The determination of knowledge levels related to doping in elite athletes - Hayri Demır; Nevzat Dıncer (Türk Spor ve Egzersiz Dergisi)
The aim of the study was to the determine knowledge level related to doping in athletes who performedindividual sports. The sample of the research consists of 117 national level athletes (62 wrestlers, 29 teakwondoplayers and 26 judoists). A personal information form and a questionnaire which aim to determine the athletes'knowledge levels and opinions about doping and ergogenic supply were carried out for the athletes participatedin the research as a means of data collection. The reliability and validity of the questionnaire were realized byEröz. The chi-square test was performed to compare variables. A significant difference was found between thesports branches about whether they intend to use doping for higher performances (X2 = 26.764; p lt; 0.01). Asignificant difference was found between sport branches about whether the athletes intend to use doping due tothe fear of losing (X2 = 43.207; p lt; 0.01). The athletes' views about whether they intend to use doping in order tocontrol their excitement were different between the sport branches (X2 = 59.035; p lt; 0.01). Opinions about whetherthe athletes had enough knowledge about doping were different between the sport branches (X2 = 16.955; p lt;0.05). The athletes' opinions about doping damages to health were found to be significant between the sportbranches (X2 = 13.742; p gt; 0.05). The athletes, who participated in this study, did not have enough knowledgeabout doping. Therefore, it may be thought that they are inclined to use doping.